A crucial role for the C‐terminal domain of exported protein 1 during the mosquito and hepatic stages of the Plasmodium berghei life cycle - Wolanin, Kamil; Fontinha, Diana; Sanches‐Vaz, Margarida; Nyboer, Britta; Heiss, Kirsten; Mueller, Ann‐Kristin; Prudêncio, Miguel (Cellular microbiology, 2019)
Intracellular Plasmodium parasites develop inside a parasitophorous vacuole (PV), a specialised compartment enclosed by a membrane (PVM) that contains proteins of both host and parasite origin. Although exported protein 1 (EXP1) is one of the earliest described parasitic PVM proteins, its function throughout the Plasmodium life cycle remains insufficiently understood. Here, we show that whereas the N‐terminus of Plasmodium berghei EXP1 (PbEXP1) is essential for parasite survival in the blood, parasites lacking PbEXP1's entire C‐terminal (CT) domain replicate normally in the blood but cause less severe pathology than their wild‐type counterparts. Moreover, truncation of PbEXP1's CT domain not only impairs parasite development in the mosquito but also abrogates PbEXP1 localization to the PVM of intrahepatic parasites, severely limiting their replication and preventing their egress into the blood. Our findings highlight the importance of EXP1 during the Plasmodium life cycle and identify this protein as a promising target for antiplasmodial intervention.